Penerapan Metode Card Sort Dalam Upaya Meningkatkan Keaktifan Siswa SDN Kedungsari 4 - Setiawan, Andika Aji; Octavia, Calista Dyah; Azzarine, Aini Savira; Hajron, Kun Hisnan (Prosiding University Research Colloquium, 2021)
The study was conducted at SDN Kedungsari 4, the subjects of this study were teachers and third grade students at SDN Kedungsari 4. The number of students was 30 students, consisting of 22 male students and 8 female students. Data collection techniques using observation and tests. The research was divided into 2 cycles, namely cycle 1 and 2. The results were cycle 1 57% and cycle 2 79%. Based on the data exposure and discussion obtained from the research results, the conclusion that can be drawn from this research is that the use of the learning model Card sort in science subjects for class III SDN Kedungsari 4 can increase student activity.